Fabrication of UiTM's energy glider / Jasmine Demi Danny Jabing, Zurriati Mohd Ali, and Zulhilmy Sahwee - Danny Jabing, Jasmine Demi; Mohd Ali, Zurriati; Sahwee, Zulhilmy (Smart Manufacturing Research Institute (SMRI), 2023)
Glider is a fixed-wing aircraft which does not depend on engine. A glider can fly for an extended period depending on the design and area of the lifting surface. Just like any other aircrafts, the design of wings is crucial to produce lift to keep aircraft fly in the air. Gliders have long wings and are designed to be lightweight which allows it to have a high lift-to-drag ratio to glide at a long distance. The maximum lift-to-drag ratio, L/Dmax can indicate how far the glider will glide as it is one of the most important performance parameters. This study aims to design, build, and fly an energy glider. Before starting on the design of the energy glider, statistical analysis has been done by comparing data from different literatures to aid in determining the initial values of the glider. Then, the general design of the energy glider has been decided during the preliminary design. To support the design decision made, ANSYS Fluent software has been used to study flow of air over KFm-5A airfoil which has been chosen during the early stages of design. The model of the energy glider was designed in CATIA V5 software before fabrication with a wingspan of 1.52 m and fuselage length of 0.69 m. Lastly, flight test was conducted to achieve the study's objectives. During the flight test, the glider reached a ceiling height of approximately 300 m and obtained a velocity of 144 km/h. The analysis of the glider performance will be used as an aircraft data for future research.